Gestión de contenido organizacional (ECM) - López, Alejandra (2013)
Enterprise Content Management makes reference to the handling of organizational content through printed or electronic means. It comprises the strategies, methods, and tools used to capture, handle, protect, preserve, and submit content and documents related to organizational processes. The ECM is employed by several organizations nowadays since it provides help in the organizational process and thanks to this, it increases the company's profitability by means of improvement of the aspects related with the organization and management of documentation. We studied the general aspects of ECM and three different products are analyzed: Alfresco, Nuxeo, and SharePoint as a ground for the comprehension of this methodology, its characteristics, scopes, benefits, and suitability. A comparison is drawn between them based on the different perspectives: cost, community support, technology, options of execution environment, etc.